Republic of Uzbekistan : 2021 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2021)
Uzbekistan embarked on an ambitious reform path in 2017, starting to liberalize its economy after years of state control. Incomes are still relatively low compared to other emerging economies. Uzbekistan entered the COVID-19 crisis with relatively strong macro-economic fundamentals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet